Enhancing the fire-resistant performance of concrete-filled steel tube columns with steel fiber-reinforced concrete - George C.; Senthil Selvan S.; Sathish Kumar V.; Murali G.; Giri J.; Makki E.; Sathish T. (Elsevier Ltd, 2025)
Due to their excellent mechanical features, concrete-filled steel tube (CFST) columns are usually employed in high-rise constructions; it is also significant to consider fire safety while designing buildings. The fire-resistance performance of fibre-reinforced CFST columns is superior to that of unreinforced CFST columns under identical conditions. The post-peak behavior of CFST columns can be enhanced by incorporating fibres to reduce the brittleness of concrete. The research on this topic is limited and considerable research gaps are available in the literature. This research examines the structural performance of steel fibre-reinforced concrete (SFRC) filled steel tubes exposed to ambient and elevated temperatures. For this purpose, fourteen CFST columns were investigated and separated into two groups. The first group of CFST columns was filled with three diverse grades of conventional concrete with and without fibres, which was subjected to ambient temperature. The second group is identical to the first group except all columns are exposed to a temperature of 1050 ?. The parameters examined were the mechanical properties of concrete, load-carrying capacity, load-deflection response, axial load, and axial strain and ductility ratio. Furthermore, using different codes, a comparison was made for the column's empirically determined load-carrying capacity with the theoretical value. Besides, the morphological characteristics of concrete were examined using energy dispersive spectroscopy (EDS), scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR) and X-ray powder diffraction (XRD). The findings show that the SFRC-filled column has superior structural qualities when subjected to elevated temperatures. At high temperatures, calcium hydroxide decomposes, and the steel tube yields, causing the column to fail by premature local bucking. ? 2023 The Authors